Layanan Pustakawan Anak terhadap Anak di Perpustakaan Proklamator Bung Hatta dalam Menumbuhkan Minat Baca Anak - Elfisa, M Khaironi; Yunaldi, Yunaldi (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2012)
The purpose of this paper is to: 1) To determine whether the Public Library of Bung Hatta can stimulate interest in reading to children, 2) to assess the development of a collection of kids reading room at the Library of Bung Hatta. Data were collected through direct observation of Bung Hatta Library and reading room librarian interviews with children as a data supplement. From the data analysis it can be concluded: (1) a reading library of Bung Hatta child is not maximized in stimulating interest in reading to children, because of the lack of services available in the reading room of the child, (2) the use of coaching in the reading room collection is not maximized in delivering child services to children. Keywords: interest in reading; collection; library Â